Golden Vaterite as a Mesoscopic Metamaterial for Biophotonic Applications. Issue 25 (13th May 2021) - Noskov, Roman E.; Machnev, Andrey; Shishkin, Ivan I.; Novoselova, Marina V.; Gayer, Alexey V.; Ezhov, Alexander A.; Shirshin, Evgeny A.; German, Sergei V.; Rukhlenko, Ivan D.; Fleming, Simon; Khlebtsov, Boris N.; Gorin, Dmitry A.; et al.
Abstract: Mesoscopic photonic systems with tailored optical responses have great potential to open new frontiers in implantable biomedical devices. However, biocompatibility is typically a problem, as engineering of optical properties often calls for using toxic compounds and chemicals, unsuitable for in vivo applications. Here, a unique approach to biofriendly delivery of optical resonances is demonstrated. It is shown that the controllable infusion of gold nanoseeds into polycrystalline sub‐micrometer vaterite spherulites gives rise to a variety of electric and magnetic Mie resonances, producing a tuneable mesoscopic optical metamaterial. The 3D reconstruction of the spherulites demonstrates the capability of controllable gold loading with volumetric filling factors exceeding 28%. Owing to the biocompatibility of the constitutive elements, "golden vaterite" paves the way to introduce designer‐made Mie resonances to cutting‐edge biophotonic applications. This concept is exemplified by showing efficient laser heating of gold‐filled vaterite spherulites at red and near‐infrared wavelengths, highly desirable in photothermal therapy, and photoacoustic tomography. Abstract : A mesoscopic biofrendly metamaterial, which includes a sub‐micrometer vaterite spherulite infiltrated with gold nanoseeds, is presented. Highly controllable gold loading leads to a variety of electric and magnetic Mie resonances, covering first and second biological transparency windows 700–1300 nm. The great potential for biophotonic applications is exemplified by demonstration of efficient spherulites laser heating at red and near‐infrared wavelengths.